2015
DOI: 10.1586/1744666x.2016.1123092
|View full text |Cite
|
Sign up to set email alerts
|

IgE-mediated mechanisms in bullous pemphigoid and other autoimmune bullous diseases

Abstract: Autoimmune bullous diseases (AIBDs) are characterized by autoantibodies against structural proteins of the dermal-epidermal junction (in pemphigoid diseases) and the epidermal/ epithelial desmosomes (in pemphigus diseases). By far, the most common AIBD is bullous pemphigoid, which is immunopathologically characterized by autoantibodies against BP180 (type XVII collagen) and BP230. IgG and, to a lesser extent, IgA autoantibodies are the major autoantibody isotypes in these disorders. IgE autoantibodies are incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 122 publications
(163 reference statements)
1
57
1
1
Order By: Relevance
“…It has been suggested that this degranulation occurs gradually, 17,24 hence contributing to blister formation. 25 Moreover, gelatinase derived from eosinophils has been reported to cleave the extracellular domain of BP180. 26 Peripheral eosinophilia has been reported in 50-60% of patients with BP in two uncontrolled retrospective cohort studies, 27,28 and is positively correlated with disease severity and time until the start of the consolidation phase.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this degranulation occurs gradually, 17,24 hence contributing to blister formation. 25 Moreover, gelatinase derived from eosinophils has been reported to cleave the extracellular domain of BP180. 26 Peripheral eosinophilia has been reported in 50-60% of patients with BP in two uncontrolled retrospective cohort studies, 27,28 and is positively correlated with disease severity and time until the start of the consolidation phase.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of other lymphocytes such as follicular helper T cells to pathogenic antibody formation in bullous skin diseases is currently under debate. 18 IgG, IgA or IgE 19 antibodies directed against structural proteins of the skin elicit the bullous pattern. They may either directly lead to keratinocyte apoptosis and loss of cellular adhesion, a concept called apoptolysis, 20 or bind to their target and cause secondary inflammation via opsonization.…”
Section: Bullous Pattern (Pattern 2b)mentioning
confidence: 99%
“…Recently, B cells are increasingly recognized as an important part of the infiltrating immune compartment in autoimmune and inflammatory skin diseases. B cell numbers are elevated in lesional skin relative to control skin specimens in a number of inflammatory diseases, including, but not limited to, psoriasis (47), pemphigus (18), lupus profundus (19,20), systemic sclerosis (scleroderma) (48), discoid lupus erythematosus (49,50), Sjögren's syndrome (51), IgG4related skin diseases (33,34), atopic dermatitis (52), and allergic contact dermatitis (53). Although an increase in skininfiltrating B cells already suggested a role for B cells in cutaneous inflammation, the therapeutic success of systemic B cell depletion with rituximab confirmed a pathogenic role for B cells in a number of these diseases (54)(55)(56).…”
Section: Skin-resident B Cells Drive Skin Inflammation: B Cell Accumumentioning
confidence: 99%